Cis‐Regulation of an m6A Eraser by an Insertion Variant Associated with Survival of Patients With Non‐Small Cell Lung Carcinoma - Lei Cheng; Qiangsheng Hu; Yanan Wang; Wei Nie; Haijiao Lu; Bo Zhang; Genming Zhao; Shiyun Ding; Feng Pan; Yinchen Shen; Runbo Zhong; Ruoxin Zhang (Advanced Science)
Abstract N6‐methyladenosine (m6A) serves as one of the crucial RNA modifications for genes involved in cancer progression. Here, 7273 expression quantitative trait loci potentially regulating 30 m6A pathway genes are identified from the GTEx database, with 69 single nucleotide polymorphisms significantly associated with survival of non‐small cell lung carcinoma (NSCLC) patients (n = 1523) from the ongoing genome‐wide association study after false positive probability tests. Notably, the rs151198415 locus, situated in a potential enhancer region, demonstrated a prolonged survival effect with the C>CCACG insertion, which is validated in an independent prospective cohort (n = 237), yielding a pooled hazard ratio of 0.72 (p = 0.007). Mechanistically, the rs151198415 C>CCACG insertion engaged in long‐range interaction with the promoter of m6A eraser ALKBH5, promoting ALKBH5 transcription by the creation of an EGR1 binding site. Then, ALKBH5 upregulated FBXL5 expression by m6A demethylation, which is dependent on the ALKBH5 H204 amino acid site and specific m6A sites on FBXL5 mRNA. Finally, the ALKBH5‐FBXL5 axis reduces intracellular reactive oxygen species levels, leading to PI3K/AKT and NF‐kB pathway inhibition and consequently suppresses NSCLC proliferation and metastasis in vitro and in vivo. Triggered by an insertion variant, this remote cis‐regulation of m6A eraser and the downstream molecular events modulate the survival of NSCLC patients.